The Optimization of Adsorption Potentials of Nigerian Kaolinite Mineral Through Acid Activation - Taofiqat Abu; H. I. Adegoke; E. O. Odebunmi (Fountain Journal of Natural and Applied Sciences (FUJNAS), 2023)
The adsorption capacities of Nigerian Kaolinite minerals obtained from Share in Kwara State in raw and acid-activated forms towards some heavy metal ions were evaluated. The clay mineral was purified by sedimentation method and modified with 0.1M nitric, sulphuric, phosphoric, acetic, and oxalic acids. The properties of the raw clay and the effects of acid activation were investigated by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier-Transform infrared spectroscopy (FTIR) and BET surface area analyses. Adsorption and desorption studies were subsequently carried out to evaluate the efficiencies of clay samples in removing Pb2+, Cd2+ and Ni2+ ions from aqueous solutions. Effects of operation parameters viz pH, initial concentration, temperature, and time on the adsorption process were determined on the raw samples, and optimum conditions obtained were utilized for evaluation on the acid-activated samples.  The acid modification was found to achieve considerable leaching of exchangeable cations on the clay mineral as confirmed by variations of the d-spacings, lowering of peak intensities and changes in absorption bands of the acid-modified samples (A-K (Acetic acid-Kaolinite), N-K (Nitric acid-Kaolinite), O-K (Oxalic acid-Kaolinite), P-K (Phosphoric acid-Kaolinite) and S-K (Sulphuric acid-Kaolinite). The surface areas increased in S-K, O-K and especially N-K (162.227 m2/g) from 114.9457 m2/g [Raw Kaolinite (R-K)] to) but reduced in A-K 112.865 m2/g and P-K (113.872 m2/g).  The activated clay samples were found to adsorb higher amounts of all the heavy metal ions studied than the raw form of the clay. Desorption analysis results revealed that the clay mineral can be regenerated and reused. Compared with other methods, modification with dilute acid provides a simple, effective, and environmentally friendly method of improving the surface characteristics of clay minerals to enhance their adsorption capacities as suitable adsorbents for water remediation purposes.